Solar-powered feed chopper for aquaculture: Toward farmer feed independence - Qory Hidayati; Aryati Muhaymin Marali; Danar Retno Sari; Yasmin Zulfati Yusrina; Hendra Sanjaya Kusno; Steven Daniel Kussoy; Candra Irawan (University of Muhammadiyah Malang, 2025)
The dependence on manufacturer feed causes high costs in farm production and, therefore, makes it susceptible to price fluctuations in the feed. This study aims to design, develop, and evaluate a solar-powered fish feed chopper suitable for off-grid aquaculture applications. The method of this study uses an engineering-based approach. It involves mechanical system design, analytical energy requirement calculations, battery sizing with depth-of-discharge considerations, and prototype fabrication. Experimental testing was conducted under solar-assisted and battery-only operating conditions using a 0.5-phase induction motor (370 W). Results showed that a six-hour no-load operation required 2,220 Wh of energy. Considering inverter losses and VRLA battery limitations, the effective safe operating time was limited to approximately three hours without solar input. A PV configuration consisting of three 200 Wp panels with an MPPT charge controller was sufficient to maintain stable daytime operation and sustain battery state-of-charge between 90–100%. The findings demonstrate that the proposed off-grid PV system can reliably support fish feed chopping operations, although system performance is constrained by battery depth-of-discharge and solar irradiance. This study confirms the feasibility of solar-powered feed choppers as a sustainable solution for small-scale aquaculture.